Bahala na.[article]. - Lagmay, Alfredo V.
A thematic apperception analysis of bahala-na-situation stories reveals character values that point to a basic psychological ascendancy in the Filipino-not submission, surrender, retreat or cessation of effort. The dynamic refected in bahala na are: the person saying it remains within the domain of the problem; he is accepting of his situation and of things as they are for the moment; he is comfortable with the unforseeable; he is tolerant of ambiguity and the risky. bahala na also generates a natural layout for improvisation in the incompletely known future encounter. It is thus suggested that, within the culture, bahala na is a positive, functional response to uncertainty.